Influencia de las acciones de responsabilidad social empresarial en el bienestar social de los trabajadores de la empresa danper trujillo s.a.c. en la planta trujillo, año 2015. - Juarez Rodriguez, Abigail (2015)
The current thesis, was expressed with the intention of establishing the "influence of the corporate SOCIAL responsibility actions in SOCIAL welfare workers of the company DANPER TRUJILLO S.A.C. in the plant TRUJILLO." To this type of research explanatory, taking as a basis the descriptive design - has been estimated explanatory, and the sample set consists of 71 workers both employees and workers of the company, with which applied the methods and techniques of quantitative and qualitative research. Reached deductions demonstrate that the actions of corporate social responsibility (RSEI) developed by Danper Trujillo S.A.C. in the Trujillo plant. contribute significantly with the welfare of the workers because it allows them to improve the following set of factors: physical and mental health, recreation and integration, labour, individual and family, which helps to maintain an adequate quality of life, knowing that the ambient through its contribution to social programs that run the company achieving improved self-esteem, growth and professional delight